Unity of the Church in the Pauline Times - Luz, Ulrich (Sacra scripta, 2004)
Ünity of Church\" in Pauline times is best understood as a continuing process towards communion. Its given real basis is Jesus Christ and the relation of the church to Israel the people of God. The basis is interpreted very differently and functions in the same time a power effective for unity and a source of dissensus. The first section analyzes this process for unity in the struggles butween Paul, the \"pillars\" and the radical Jewish Christians. The thesis is that all three contrahents, Paul, James the brother of Jesus and the radical Jewish Christians, are engaged for the unity of the church in their way. The second section analyzes the ïnstruments of unity\" through which Christ is at work in the Pauline churches. Emerging ecclesiological concepts, such as \"people of God\" and \"body of Christ\", are secondary to the experiences of communion in history and mirror them.